The Communist Party in local key: old strategies in a new political scenario. Río Cuarto, Córdoba (1945-1951) (Quinto Sol, 2016)
The studies on the relationship between peronism and communism are silent on their features in the inland or on the concrete practices that resulted. This article seeks to explain this from its approach in a local area, the city of Rio Cuarto. It is understood that both the particular characteristics of the initial formation of peronism in it, as well as tradition in front-like strategies and the influence over local unions that communism had, provided such relations with its own dynamics that would complement and refine the reconstructions that upon them have been made from central historiographical spaces.
Keywords: Communist Party; peronism; local places; Río Cuarto